Access and utilization of mental health services for immigrants and refugees: Perspectives of immigrant service providers - Salami, Bukola; Salma, Jordana; Hegadoren, Kathleen (International journal of mental health nursing, 2019)
Immigrant and refugee populations experience life stressors due to difficult migration journeys and challenges in leaving one country and adapting to another. These life stressors result in adverse mental health outcomes when coupled with a lack of adequate support‐enhancing resources. One area of support is access to and use of mental health services to prevent and address mental health concerns. Immigrant service providers in Canada support the integration and overall well‐being of newcomers. This study focuses on immigrant service providers’ perceptions of access to and use of mental health services for immigrants and refugees in Alberta. A qualitative descriptive design was used to collect and analyse the perspectives of 53 immigrant service providers recruited from nine immigrant serving agencies in Alberta between November 2016 and January 2017. Data were collected using a combination of individual interviews and focus groups, followed by thematic data analysis to identify relevant themes. Barriers to access and use of mental health services include language barriers, cultural interpretations of mental health, stigma around mental illness, and fear of negative repercussions when living with a mental illness. Strategies to improve mental health service delivery include developing community‐based services, attending to financial barriers, training immigrant service providers on mental health, enhancing collaboration across sectors in mental health service delivery, and advancing the role of interpreters and cultural brokers. Overall, immigrant service providers present a nuanced view of the complex and inter‐related barriers immigrants and refugees experience and identify potential approaches to enhancing mental health service delivery.